Confidence, bond risks, and equity returns - Zhao, Guihai (Journal of Financial Economics, 2017)
I show that investor confidence (size of ambiguity) about future consumption growth is driven by past consumption growth and inflation. The impact of inflation on confidence has moved considerably over time and switched on average from negative to positive in 1997. Motivated by this evidence, I develop and estimate a model in which the confidence process has discrete regime shifts, and I find that the time-varying impact of inflation on confidence enables the model to match bond risks over different subperiods. The model can also account for stock and bond return predictability, and correlation between price-dividend ratios and inflation, among other features of the data.